Factors and Levels of Student Engagement in a State College: A Mixed-Methods Study - Enerio, Antonio Jr. (Technium Social Sciences Journal, 2021)
This sequential explanatory mixed-methods study determined the factors and levels of student engagement among the 493 students in Northwestern Mindanao State College of Science and Technology, Tangub City, Philippines. The quantitative data gathered using survey questionnaires revealed the following: the students’ levels of perception on the importance of competence, autonomy, relatedness, student-teacher transaction, and student-institution transaction to students’ engagement are very important; the levels of affective engagement, cognitive engagement, and behavioral engagement are very high, and social engagement is high; the factors and levels of student engagement have positive correlation; and the student-teacher transaction is the best predictor of student engagement. Using in-depth interviews of 12 participants picked using criterion purposive sampling, the qualitative data, analyzed using Braun and Clarke analysis, arrived at nine themes for the importance of the factors to students’ engagement and 15 themes for the students’ engagement in the four dimensions. The factors of student engagement are important since students are given the freedom to accomplish their dreams and develop themselves through good relationships with classmates, desirable personal and professional qualities of the teachers, and the support of the college. The students’ engagement in the four dimensions can be attributed to the goals that they have to achieve, the support from teachers and the school, their active participation, the guidance from the more knowledgeable others and the harmonious relationship with peers. It is recommended that the College invest in various support services to create a pleasant learning environment, devote itself to faculty training to prepare them for teaching, and implement activities that will enhance student engagement.